DYSPHEMISM USED IN PROHABA NEWSPAPER - Intan Maulana; Zulfadli A. Aziz; Bukhari Daud (English Education Journal, 2020)
The unique use of language plays an important role in media, especially for the journalist business like newspapers. As a strategy to develop journalistic business, many mass media work hard to attract the reader's attention, such as the use of language style of dysphemism. This research aimed at finding out the types of dysphemism and its function contained in Prohaba Newspaper, a daily newspaper published in Banda Aceh. In this qualitative research, the data were obtained from the newspaper published in June-December Edition 2018. The data were analyzed and categorized based on the types of dysphemism proposed by Warren (1992) and its functions by Allan and Burridge (2006). It was found that Prohaba  contains the five types of dysphemism with their own functions. Out of 26 dysphemism, the most dominant dysphemism type, 14 cases, that was found in this research was dysphemism with the function to insult. Term of insult or disrespect type was found in three pieces of news which compared people to animals. Furthermore, taboo terms were used in other three pieces of news, and the last three of news used euphemistic dysphemism type.